The Effect of Arm Muscle Strength and Leg Muscle Explosiveness on Ball Shooting Results Basketball - Jumanza, Rafi; Lian, Bukman; Manullang, Jujur Gunawan (PPSDP International Journal of Education, 2024)
The problem in this study is the lack of students in basketball shooting results so that the players often experience failures. The formulation of the problem in this study is whether there is an effect of arm muscle training and leg muscle explosive training on shooting results in extracurricular students of SMP Negeri 2 Bangka Barat. The purpose of this study is to find out whether there is an effect of arm muscle training and leg muscle explosiveness training on shooting results in extracurricular students of SMP Negeri 2 Bangka Barat. The method used in this study is the one group experiment method. The sample in this study is the total of the existing population, namely 26 students who participate in extracurricular activities at SMP Negeri 2 Bangka Barat. Based on the results of the research and the results of statistical calculations on the test of improving the results of arm muscle strength exercises to influence arm muscle strength and leg muscle explosiveness on basketball shooting results in extracurricular students of SMP Negeri 2 Bangka Barat, the author can conclude that: isometric exercises have an effect on basketball shooting in extracurricular basketball games of SMP Negeri 2 Bangka Barat. The magnitude of the influence is shown significantly at the real level of 0.05 with t calculated > t 0.95 (50) = 6.84 > 1.70.